2019
DOI: 10.3390/ijerph16060983
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ascorbic Acid on Osteopontin Expression and Axonal Myelination in the Developing Cerebellum of Lead-Exposed Rat Pups

Abstract: Osteopontin (OPN) is a multi-functional protein that binds to integrin and calcium-binding phosphoprotein. OPN is required for normal neuronal development and its axonal myelination. We studied the combined effect of lead (Pb) and ascorbic acid treatment on OPN expression in the developing cerebellum. We randomly divided pregnant female rats into three groups: control, Pb (lead acetate, 0.3%, drinking water), and Pb plus ascorbic acid (PA; ascorbic acid, 100 mg/kg, oral intubation) groups. The blood level of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 51 publications
5
14
0
2
Order By: Relevance
“…Further, Pb-induced rats showed decreased ( p < 0.05) cerebellar weights, which could be attributed to the marked degeneration of the cerebellar cells observed. These results are in accordance with several preceding studies [9,37,48,72,73] that reported similar findings of neuronal degeneration in Pb and other heavy metal toxicity on the cerebellums, with more consequences for the Purkinje cells due to sensitivity of the Purkinje cell layer. Further, previous studies also documented the toxic effect of Pb administration on juvenile and young rats, resulting in different neurological impairments in various parts of the brain and nervous system [74,75,76,77].…”
Section: Discussionsupporting
confidence: 93%
“…Further, Pb-induced rats showed decreased ( p < 0.05) cerebellar weights, which could be attributed to the marked degeneration of the cerebellar cells observed. These results are in accordance with several preceding studies [9,37,48,72,73] that reported similar findings of neuronal degeneration in Pb and other heavy metal toxicity on the cerebellums, with more consequences for the Purkinje cells due to sensitivity of the Purkinje cell layer. Further, previous studies also documented the toxic effect of Pb administration on juvenile and young rats, resulting in different neurological impairments in various parts of the brain and nervous system [74,75,76,77].…”
Section: Discussionsupporting
confidence: 93%
“…Further, Pb-induced rats showed decreased (P<0.05) cerebellar weight, which could be attributed to the marked degeneration of the cerebellar cells observed. These results are in accordance with several preceding studies[9,19,31,49,50] that reported similar findings of neuronal degeneration in Pb and other heavy metals toxicity on the cerebellum with more consequences on the purkinje cells due to sensitivity of the purkinje cells layer. However, treatment with curcumin reverses the above mentioned Pb-induced morphological aberrations in the rats.…”
supporting
confidence: 93%
“…This present study decided to use ICP-MS for its showed decreased (P<0.05) cerebellar weight, which could be attributed to the marked degeneration of the cerebellar cells observed. These results are in accordance with several preceding studies [9,26,37,54,55] that reported similar findings of neuronal degeneration in Pb and other heavy metals toxicity on the cerebellum with more consequences on the purkinje cells due to sensitivity of the purkinje cells layer. However, treatment with curcumin reverses the above mentioned Pb-induced morphological aberrations in the rats.…”
Section: Discussionsupporting
confidence: 93%